Examining the impact of multi-layer graphene using cellular and amphibian models. (13th April 2016) - Muzi, Laura; Mouchet, Florence; Cadarsi, Stéphanie; Janowska, Izabela; Russier, Julie; Ménard-Moyon, Cécilia; Risuleo, Gianfranco; Soula, Brigitte; Galibert, Anne-Marie; Flahaut, Emmanuel; Pinelli, Eric; Gauthier, Laury; et al.
Abstract: In the last few years, graphene has been defined as the revolutionary material showing an incredible expansion in industrial applications. Different graphene forms have been applied in several contexts, spreading from energy technologies and electronics to food and agriculture technologies. Graphene showed promises also in the biomedical field. Hopeful results have been already obtained in diagnostic, drug delivery, tissue regeneration and photothermal cancer ablation. In view of the enormous development of graphene-based technologies, a careful assessment of its impact on health and environment is demanded. It is evident how investigating the graphene toxicity is of fundamental importance in the context of medical purposes. On the other hand, the nanomaterial present in the environment, likely to be generated all along the industrial life-cycle, may have harmful effects on living organisms. In the present work, an important contribution on the impact of multi-layer graphene (MLG) on health and environment is given by using a multifaceted approach. For the first purpose, the effect of the material on two mammalian cell models was assessed. Key cytotoxicity parameters were considered such as cell viability and inflammatory response induction. This was combined with an evaluation of MLG toxicity towards Xenopus laevis, used as both in vivo and environmental model organism.